If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 4(6x + -9) = 24x + -36 Reorder the terms: 4(-9 + 6x) = 24x + -36 (-9 * 4 + 6x * 4) = 24x + -36 (-36 + 24x) = 24x + -36 Reorder the terms: -36 + 24x = -36 + 24x Add '36' to each side of the equation. -36 + 36 + 24x = -36 + 36 + 24x Combine like terms: -36 + 36 = 0 0 + 24x = -36 + 36 + 24x 24x = -36 + 36 + 24x Combine like terms: -36 + 36 = 0 24x = 0 + 24x 24x = 24x Add '-24x' to each side of the equation. 24x + -24x = 24x + -24x Combine like terms: 24x + -24x = 0 0 = 24x + -24x Combine like terms: 24x + -24x = 0 0 = 0 Solving 0 = 0 Couldn't find a variable to solve for. This equation is an identity, all real numbers are solutions.
| 3x+11=-52 | | 12n+9=9+5t | | -34=6(3k+8) | | 19=3j+1 | | (3x-7)(x-3)=-16 | | 28=9x-21x+24 | | 4[2a+3]=-3[a+-1]+31 | | 3(3-x)+4=34 | | 7-8+(-3)+(-5)= | | 840= | | X-(3-x)=x+5 | | 4[2a+3]=-3[a-1] | | (3x+7)(x-7)=-16 | | 5x+(x+3)+(x+3)=120 | | (3x-3)=(4x-11) | | -4(x-6)=20 | | -30x-20=5x+7 | | (3v-1)(v-1)=0 | | 3x^2-7=10 | | -30=5x+7 | | 20+4h=14h | | 6x+3-(8x)=13 | | 6x+3-(8)x=13 | | (-7)-(-5)+(-6)= | | 360=(x-5)+(x+35)+x+1.4x | | 2(-0.38)-3= | | 3x+3y+x+y+z= | | 5(8+6n)=7-3n | | -(b+4)-b=4-(1+3b) | | 7(x+3)+4=-31 | | 6m^3+10m^2=0 | | 800+6m=1000+10m |